A SINGLE LONG-TERM EFFECT OF STRESSORS VARIOUS-TERM NATURE OF THE DEVELOPMENT OF DIC-SYNDROME IN RATS - V. I. Kiselev; I. I. Shakhmatov; V. M. Vdovin; N. A. Lycheva; O. V. Alekseeva; Yu. A. Bondarchuk; V. Yu. Nikolaev (Бюллетень сибирской медицины)
The aim of the study was to determine the mechanism of the hemostasis system response to the stressors of various nature at successively increasing duration of exposure to stress. Physical exertion, hypothermia and hyperthermia were simulated as stress influences. Wistar type of rats was used as the object of the research. The data of vascular-thrombocyte and coagulative hemostasis as well as anticoagulative and fibrinolytic system activity were investigated. One-type reaction independent of irritant nature was observed during the investigation. As a responce to a single short-term exposure to an irritant the combined activation of aggregative platelet function, contact phase of blood coagulation as well as anticoagulative and fibrinolytic system is registered. As the exposure was prolonged successive involment of all the hemostasis system components into reciprocal response was registered in the bloodstream of the experimental animals. By the end of a single peak term exposure the totality of hemostasis features characteristic of the initial stage of DIC-syndrome was markedly registeredin experimental animals.When considering physical exertion it can be concluded that latent thrombin genesis firstly appeared after four hours of exposure increased dramatically by the end of eight hours stress. Similar picture of progressing thrombinemia is observed when analyzing the effect of hypothermia on hemostasis. Thus firstly registered after 30 minutes of hypothermia exposure the markers of thrombin genesis were eliminated from the blood stream in the process of thrombi formation by the end of the experimental exposure. Furthermore the rheological properties of blood in experimental animals were impaired as a result of a marked decrease of blood plasma fibrinolytic activity. When analyzing the effect of hyperthermia on hemostasis the manifested thrombinemia (at thermal exposure for 20 minutes) was shown to change to the picture characteristic of developed DIC-syndrome after 30 minutes of hypothermal exposure.Thus, on the basis of the results obtained during the experiments and described in this article, it can be assumed that the stress factors with prolonged exposure causing successively increasing signs of distress on the part of the hemostatic system. At increased exposure the signs of distress of the hemostasis system are successively increasing. It is manifested in the appearance and then augmenting of thrombinemia signs on the background of oppression of blood plasma fibrinolytic activity and reducing the anticoagulants concentration. It is necessary to consider the obtained results in situations accompanied by stress influence. Hemostasis picture demonstrates the impairment of the rheological properties of blood up to the development of DIC-syndrome at increased duration of exposure to stress.